2009
DOI: 10.1007/s00167-009-0862-5
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate cement enhances primary stability of open-wedge high-tibial osteotomies

Abstract: We investigated if injectable calcium phosphate cement improves primary stability in open-wedge high-tibial osteotomy. A 10 mm open-wedge osteotomy was performed on eight pairs of preserved cadaver tibiae and seven pairs of composite (Sawbone) left tibiae. Osteosynthesis was performed with the Dynafix plate system. The gap resulting from surgery either was filled with 15 g injectable calcium phosphate cement in half the bones or was left untreated. The composite tibiae were loaded at a ramp speed of 20 mm/min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…However, we did also find that the implant itself seemed to be stable enough to withstand the loadings found during walking. 16 This might be the reason why the migration in the two bone graft groups also was small in the present study. The patients were aligned to 4 degrees of valgus and kept the alignment throughout the study period.…”
Section: Discussionmentioning
confidence: 62%
“…However, we did also find that the implant itself seemed to be stable enough to withstand the loadings found during walking. 16 This might be the reason why the migration in the two bone graft groups also was small in the present study. The patients were aligned to 4 degrees of valgus and kept the alignment throughout the study period.…”
Section: Discussionmentioning
confidence: 62%
“…Merck‐CPC was formulated from a powder phase of 61% α‐TCP, 26% calcium phosphate (CaHPO 4 ), 10% calcium carbonate (CaCO 3 ), and 3% hydroxyapatite (Plasma Biotal, Derbyshire, UK) and a liquid phase of 4 wt % di‐sodium hydrogen phosphate (Na 2 HPO 4 ) (Fisher Scientific, Leicestershire, UK) in deionized water mixed at a liquid‐to‐powder ratio of 0.35 mL/g. It is based on a commercial formulation developed by Merck KGaA (Darmstadt, Germany) to have a similar chemical composition and crystalline structure with that of the mineral phase of bone . The PMMA cement used was Vertebroplastic Radiopaque Resinous Material (DePuy, Leeds, UK), which is a commercially available cement routinely used clinically for vertebroplasty (referred to herein as VP‐PMMA).…”
Section: Methodsmentioning
confidence: 99%
“…It is based on a commercial formulation developed by Merck KGaA (Darmstadt, Germany) to have a similar chemical composition and crystalline structure with that of the mineral phase of bone. 37 The PMMA cement used was Vertebroplastic Radiopaque Resinous Material (DePuy, Leeds, UK), which is ORIGINAL RESEARCH REPORT JOURNAL OF BIOMEDICAL MATERIALS RESEARCH B: APPLIED BIOMATERIALS | FEB 2016 VOL 104B, ISSUE 2 a commercially available cement routinely used clinically for vertebroplasty (referred to herein as VP-PMMA).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous basic science papers support the concept of calcium phosphate cement as a bone graft substitute that carries osteoconductive properties utilized in both tibial plateau fracture treatment and supplementation to owHTO fixation [23, 25, 36, 37]. Biomechanical studies utilizing cadaveric tibia have shown that calcium phosphate cement provides significantly increased compressive strength and stiffness compared to autograft iliac bone graft [25, 37].…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical studies utilizing cadaveric tibia have shown that calcium phosphate cement provides significantly increased compressive strength and stiffness compared to autograft iliac bone graft [25, 37]. In particular, Lind‐Hansen et al [23] demonstrated in cadaver tibiae that the injection of calcium phosphate cement increases the initial stability of high tibial osteotomy fixation when the specimens were loaded in compression. To date, only one other study has identified torsional load as an important variable after owHTO [35], but rotational forces are placed on the knee during a normal gait cycle, which is therefore an important aspect of construct design for an ambulatory patient after owHTO [12].…”
Section: Introductionmentioning
confidence: 99%